DEVELOPMENT OF INFORMATICS TECHNOLOGY AND COMPUTER BOOK BASED ON 4D MODELS - Anna Mariyani; Muhammad Aunur Rofiq; Tio Ikhtiar Tiantoko (UICELL, 2021)
This study aims to develop a textbook on the subject of Information Technology and Computers with a self-regulated learning approach. This research uses Development and Research method through 4D Model. The definition stage is carried out by determining the characteristics of the textbook that will be developed through the initial study. The design stage, namely by choosing the format and design of the textbook to produce the first correction (draft). The development stage is carried out to produce the second draft, third correction, and the final product of the textbook. The second correction is obtained through the revised expert validation results that have been recommended. The third correction is the acquisition of small group test results by taking randomly. Based on the results of field tests on students who are taking Computer Information and Technology courses, the final product is obtained from the textbook. One of the textbook features and tools developed is the project task feature. Based on the validation of the textbook and its supporting tools, the criteria are very feasible and ready to be used and can guide student learning independently through the features in the textbook. The development of this textbook is expected to help in developing not only Information Technology and Computers but also other materials that use computers. Keywords: RnD, 4D Model, Informatic Technology, Learning Development